Analisis Pengaruh Kualitas Sistem dan Kualitas Informasi Terhadap Manfaat Bersih Melalui Kepuasan Pengguna Sistem Informasi Akademik - Zubdatu Zahrati (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
This study aims to determine the effect of system quality and information quality on net benefits through user satisfaction of academic information systems. The research method used is a quantitative method. Respondents in this study were students of the 2024-2025 class at Cipta Wacana Christian University with a sample of 81 respondents. Indicators on the system quality variable are system flexibility, system integration, time to respond, error recovery, convenience of access, language, easy to use, reliability, documentation of the system, security of data, navigation. Indicators on the information quality variable are completeness, precision, reliability, currency, format of output, relevance, accurate, timeless, detail, order. Indicators on user satisfaction are repeat purchases, repeat visits, efficiency, effectiveness, satisfaction. Indicators on the net benefit variable are speed of accomplishing tasks, job performance, task productivity, effectiveness, ease of job, usefulness, cost reduction, decision making. Data analysis technique used Partial Least Square. Results of the study are all indicators in each variable are valid and each variable has met the reliability criteria. R-square value of 80.4% indicates that variations in system quality and information quality, and user satisfaction can contribute to explaining the variance of the net benefit variable. Results of the hypothesis testing indicate that there is no influence between system quality and information quality on net benefits. However, the user satisfaction variable is able to mediate between system quality and information quality on net benefits.